1. Online Learners’ Interest in Collaborative Tools - Kane, Tom; Baggaley, Jon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
An online survey was conducted (June 2001) of attitudes of distance education (DE) learners/teachers to online collaborative tools. The respondents in the study were 135 graduate students and faculty members of Athabasca University’s Centre for Distance Education (CDE). They demonstrated particular interest in tools that offer the following features: file sharing, automatic synchronisation of documentation for the group, audio conferencing, text chat, and privacy. They also expressed useful opinions on topics including their willingness to upgrade their computer systems, and to pay to avoid online product advertising. These results will be useful in the selection of appropriate new methods for online instruction.